Studies on the Storage Stability of Chicken Meat Pickle with Lime Juice - Indumathi, J.; Reddy, B. Obula; Reddy , G.V. Bhaskar (Journal of Meat Science, 2015)
Lime juice is proposed as preservative for increasing the shelf life of chicken meat pickle. This study evaluated the antioxidant and antimicrobial activity of lime juice incorporated in chicken meat pickle at two different levels of 5% (T1) and 10% (T2). The chicken meat pickle was packed aerobically in 250 g polyethylene terepthalate (PET) jars and then stored at room temperature for 80 days under retail display conditions for evaluation of different physico chemical, microbiological and sensory characteristics at regular interval of 20 days. Use of lime juice substantially brought down the pH and acidity of pickle, whereas it did not significantly (p>0.05) influenced the peroxide value, % FFA and 2- TBARS values of chicken meat pickle during 80 days of storage. Microbiological counts did not show substantial change and remained satisfactory throughout the 80 days of storage period. Neither storage period nor two levels of lime juice significantly (p>0.05) influenced the standard plate count of chicken meat pickle stored at room temperature. Yeast & moulds and coliforms were not observed up to 20 and 40 days of storage period respectively in the both the treatments. The sensory evaluation showed that chicken meat pickle added with 5 % lime juice (T1) was preferred compared to the 10% lime juice (T2).